2022
DOI: 10.1186/s40645-022-00475-6
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric resuspension of insoluble radioactive cesium-bearing particles found in the difficult-to-return area in Fukushima

Abstract: The deposition of insoluble radiocesium-bearing microparticles (CsMPs), which were released from the Fukushima Daiichi Nuclear Power Plant (F1NPP) accident in March 2011, has resulted in the widespread contamination of eastern Japan. Obviously, these deposited insoluble CsMPs may become the secondary contamination sources by atmospheric migration or other environmental transferring process; however, the understanding of the transport mechanism remains non-elucidation, and the relevant evidence has not been dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…These CsMPs transferred to the Kanto region were found to have originated from Unit 2 based on their shapes, elemental compositions, and 134 Cs/ 137 Cs radioactivity ratios. Some studies have suggested the possibility of the resuspension of CsMPs that have settled on the ground 18 , 19 . CsMPs are extremely small particles and are easily taken up into the body by inhalation; they have the potential to remain in organs such as the lungs for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…These CsMPs transferred to the Kanto region were found to have originated from Unit 2 based on their shapes, elemental compositions, and 134 Cs/ 137 Cs radioactivity ratios. Some studies have suggested the possibility of the resuspension of CsMPs that have settled on the ground 18 , 19 . CsMPs are extremely small particles and are easily taken up into the body by inhalation; they have the potential to remain in organs such as the lungs for a long time.…”
Section: Introductionmentioning
confidence: 99%